Classical Absences (1896–2017). (30th August 2021) - Jansen, Laura
Abstract: When we consider classical receptions in terms of presences, we often think of how antiquity materializes visibly and/or substantially in the fabric of our histories, whether as physical remains or concrete traditions. Yet the search for the classical as a solid, conspicuous phenomenon reveals only one side of the fascinating story of how we can conceive its status and circulation across space and time. This article investigates some key examples across the period 1896–2017, from Argentine author J. L. Borges to British poet-translator Josephine Balmer, which disclose the flip side of this story—that of antiquity's existence on various levels of dispersal, silence, and occlusion at the intersections of poetry, mythopoeic biography, legend-making, and creative translation. It argues that, in their engagement with the Greco-Roman past, these examples both advance our understanding of absence as a critical idiom and question our sense of how antiquity makes its impact on our world as a 'classical presence'.